2009
DOI: 10.1186/1754-9493-3-24
|View full text |Cite
|
Sign up to set email alerts
|

Is the intraosseous access route fast and efficacious compared to conventional central venous catheterization in adult patients under resuscitation in the emergency department? A prospective observational pilot study

Abstract: Background: For patients' safety reasons, current American Heart Association and European Resuscitation Council guidelines recommend intraosseous (IO) vascular access as an alternative in cases of emergency, if prompt venous catheterization is impossible. The purpose of this study was to compare the IO access as a bridging procedure versus central venous catheterization (CVC) for in-hospital adult emergency patients under resuscitation with impossible peripheral intravenous (IV) access. We hypothesised, that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 52 publications
3
46
1
9
Order By: Relevance
“…1,8,9 Furthermore, prospective studies have demonstrated superior speed of insertion with IO devices compared with the central venous catheter, which is generally considered the back-up technique for failed peripheral IV attempts. 10,11 Although the use of IO devices is rapidly expanding for patients requiring fluid and cardiac resuscitation, 1,9 some have expressed concern about their safety, especially in the setting of blood product transfusion. 12 Despite these concerns, the European Resuscitation Council Guidelines, 13 the American Heart Association Advanced Cardiac Life Support (ACLS) 14 and the American College of Surgeons Advanced Trauma Life Support (ATLS) 15 all support the use of IO devices for adult patients in extremis.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,9 Furthermore, prospective studies have demonstrated superior speed of insertion with IO devices compared with the central venous catheter, which is generally considered the back-up technique for failed peripheral IV attempts. 10,11 Although the use of IO devices is rapidly expanding for patients requiring fluid and cardiac resuscitation, 1,9 some have expressed concern about their safety, especially in the setting of blood product transfusion. 12 Despite these concerns, the European Resuscitation Council Guidelines, 13 the American Heart Association Advanced Cardiac Life Support (ACLS) 14 and the American College of Surgeons Advanced Trauma Life Support (ATLS) 15 all support the use of IO devices for adult patients in extremis.…”
Section: Discussionmentioning
confidence: 99%
“…Success rates of central venous canulation and IO access were compared in 10 trauma patients on whom peripheral vascular access could not be achieved after three attempts for a maximum of two minutes; first attempt success rate was 90% for IO access and 60% for central venous access. Mean procedure time was significantly shorter for IO cannulation ( 2.3 min) compared to central line placement (9.9 min) [13] . We preferred to use EZ -IO device in our study due to its easy application.…”
Section: Discussionmentioning
confidence: 96%
“…Delayed treatment for these patients due to insufficient vascular access can lead to increased mortality. Several studies have demonstrated that intraosseous lines can be placed significantly faster than central lines [17,18]. Therefore, intraosseous assess should be considered by RRTs or critical care physicians when patients lacking appropriate vascular access begin to clinically deteriorate.…”
Section: Discussionmentioning
confidence: 99%